2021
DOI: 10.34117/bjdv7n2-500
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento in Vitro De Cyrtopodium Cachimboense L. C. Menezes Em Diferentes Níveis De Sacarose / in Vitro Development of Cyrtopodium Cachimboense L. C. Menezes in Different Levels of Sucharose

Abstract: RESUMOO presente trabalho teve como objetivo analisar os efeitos de diferentes concentrações de sacarose no desenvolvimento in vitro de protocormios Cyrtopodium cachimboense L. C. Foram utilizados protocormios de Cyrtopodium cachimboense L. C. obtidos da germinação de sementes em meio de cultura alternativo, sem a presença de carvão, o delineamento experimental foi inteiramente casualizado. Após 90 dias a partir da germinação da semente, 5 protocormios foram transferidos para cada frasco com capacidade para 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…Regarding sucrose, the optimal results for in vitro cultivation of B. tuberculata were achieved with concentrations around 15 and 30 g L -1 . Studies on different sucrose concentrations in the in vitro culture of native orchids, such as Alatiglossum fuscopetalum (Ferreira et al, 2017), Oncidium flexuosum (Caovila et al, 2016), Cyrtopodium cachimboense (Paulino et al, 2021), Miltonia flavescens (Lemes et al, 2014), and Cattleya schilleriana (Galdiano-Júnior et al, 2018), support our results. However, in contrast to our findings, Silva et al (2014) observed that Cattleya walkeriana Gardner plants exhibited increased root system growth when cultured with the highest tested sucrose concentration (45 g L -1 ) in flasks with ventilation caps.…”
Section: In Vitro Growthsupporting
confidence: 85%
“…Regarding sucrose, the optimal results for in vitro cultivation of B. tuberculata were achieved with concentrations around 15 and 30 g L -1 . Studies on different sucrose concentrations in the in vitro culture of native orchids, such as Alatiglossum fuscopetalum (Ferreira et al, 2017), Oncidium flexuosum (Caovila et al, 2016), Cyrtopodium cachimboense (Paulino et al, 2021), Miltonia flavescens (Lemes et al, 2014), and Cattleya schilleriana (Galdiano-Júnior et al, 2018), support our results. However, in contrast to our findings, Silva et al (2014) observed that Cattleya walkeriana Gardner plants exhibited increased root system growth when cultured with the highest tested sucrose concentration (45 g L -1 ) in flasks with ventilation caps.…”
Section: In Vitro Growthsupporting
confidence: 85%